Uji Validasi dan Reliabilitas Kuesioner SF-36 Versi Bahasa Indonesia untuk Mengukur Kualitas Hidup Pasien Hemodialisa Gagal Ginjal Kronis - Indriswari, Baiq; Apriliany, Fitri; Novitarini (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2025)
Chronic kidney disease (CKD) not only impacts physiological aspects but also reduces the patient's quality of life. Assessment of the quality of life is important as an indicator of the success of therapy and disease management. This study aims to determine the validity and reliability of the Indonesian version of the Short Form-36 questionnaire in measuring the quality of life of CKD patients undergoing hemodialysis. This study used a descriptive cross-sectional design with a prospective approach. Data were collected by completing the Short Form-36 questionnaire by CKD patients undergoing outpatient care at RSUD Mataram. Validity analysis was performed using Pearson correlation, while reliability was tested with Cronbach's alpha. The number of respondents was 30 patients. The results showed that the Short Form-36 questionnaire had a Pearson correlation value > 0.40 and a Cronbach's alpha value > 0.70, indicating that this instrument is valid and reliable. Thus, the Indonesian version of the Short Form-36 questionnaire can be used to assess the quality of life of CKD patients.